2010
DOI: 10.1007/s13146-010-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Continental paleoclimate estimates from the late Mississippian Redwall karst event: northern and north-central Arizona (USA)

Abstract: The Redwall Limestone of northern and northcentral Arizona (USA) was investigated to determine if suitable secondary silica precipitates were present and which could be used to estimate continental weathering temperatures for the late Carboniferous period. Secondary (authigenic) silica precipitates in lag deposits of chert and residual rubble breccia of oxidized and durable earth material under subaerial weathering during karst events. The Redwall Limestone was extensively karsted for millions of years during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Kenny and Knauth [ 46 ] demonstrated that oxygen and hydrogen isotopic composition of secondary (authigenic) silica precipitated in palaeokarst chert lags could be used to estimate near-surface continental weathering temperatures as far back as the Late Proterozoic. Kenny [ 47 ] reported continental weathering temperatures inferred from oxygen and hydrogen measurements of secondary silica precipitated during a tropical karst event that developed on the Mississippian Redwall Limestone of northern AZ (USA). Abruzzese et al [ 63 ] suggested that oxygen and hydrogen isotope ratios of freshwater chert could be used as an indicator of regional climatic variation in the Cenozoic and concluded that early diagenetic chert likely record surface conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenny and Knauth [ 46 ] demonstrated that oxygen and hydrogen isotopic composition of secondary (authigenic) silica precipitated in palaeokarst chert lags could be used to estimate near-surface continental weathering temperatures as far back as the Late Proterozoic. Kenny [ 47 ] reported continental weathering temperatures inferred from oxygen and hydrogen measurements of secondary silica precipitated during a tropical karst event that developed on the Mississippian Redwall Limestone of northern AZ (USA). Abruzzese et al [ 63 ] suggested that oxygen and hydrogen isotope ratios of freshwater chert could be used as an indicator of regional climatic variation in the Cenozoic and concluded that early diagenetic chert likely record surface conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen and hydrogen isotopic compositions of silica have been successfully used to better understand the crystallization history of chert [ 45 ] based on the premise that once the granular, microcrystalline quartz has crystallized the isotopic composition is preserved. Kenny and Knauth [ 46 ] and Kenny [ 47 ] demonstrated that oxygen and hydrogen isotopic composition of secondary (authigenic) silica crystallized during subaerial exposure surfaces could be used to approximate near-surface continental weathering temperatures. Both crystallization temperatures and the role of meteoric waters in the initial crystallization of silica can be gleaned from the stable isotope values.…”
Section: Introductionmentioning
confidence: 99%